Societies large and small: On the rhetoric of the Third Section under Nicholas I - S. M. Voloshina (Шаги, 2023)
The article examines the evolution of the perception of the word «society» and its derivatives in documents of the Third Section during the reign of Nicholas I. The two distinct meanings of the word were used to refer to two traditional objects of surveillance by the secret police: society as a whole and a smaller part of it, an organization. While presenting its vision and analysis of «societies» of different levels in annual reports and current files, the Third Section simultaneously recorded the perception of public opinion by the state authorities, and acted as a meaning-forming institution that determined what exactly should be considered a society. Changes in the vocabulary used in the documents to describe different types of «societies» and such derivatives as «public opinion» (literally – «opinion by society») reflect both political changes in the country and power practices. Whereas the first annual reports by the Third Section (from 1827 on) widely use the term «public opinion» (but only as a direct translation from the French, the language of the documents), the authors of the later reports totally avoid it. In addition, they tend to avoid the usage of «society» in the narrow sense, replacing it with various synonyms (such as «gathering» or «a bunch of»). During the last and most severe seven years of the reign of Nicholas I, the word «society» (in the broad sense) acquires a new meaning: the aggregate of people who are loyal to the tsar and the political regime.